2014
DOI: 10.1002/alr.21456
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is deficient in nasal polyps: implications for the pathogenesis of the disease

Abstract: Autophagy is deficient presumably due to suppression by high Akt-mTOR activity in nasal polyps, which may provide a molecular basis for future mechanistic study of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…Recent reports provide some clues concerning the potential role of autophagy in patients with CRS by demonstrating autophagy deficiency in NPs and its inverse correlation with COX-2 expression. 20,21 However, no study has sought to assess the direct role of autophagy in the development of CRS, especially ECRS. In the present study we obtained evidence indicating that autophagy deficiency in myeloid cells, particularly macrophages, is linked to PGD 2 dysregulation and eosinophilic inflammation in a murine model of ECRS.…”
mentioning
confidence: 99%
“…Recent reports provide some clues concerning the potential role of autophagy in patients with CRS by demonstrating autophagy deficiency in NPs and its inverse correlation with COX-2 expression. 20,21 However, no study has sought to assess the direct role of autophagy in the development of CRS, especially ECRS. In the present study we obtained evidence indicating that autophagy deficiency in myeloid cells, particularly macrophages, is linked to PGD 2 dysregulation and eosinophilic inflammation in a murine model of ECRS.…”
mentioning
confidence: 99%
“…In asthma, genetic polymorphisms in the autophagy genes can increase the susceptibility of airway epithelial cells to the severe respiratory viral infection . Very recently, three preliminary studies have reported conflicting results regarding the autophagy status in nasal polyp‐derived fibroblast, arguing for further investigations on the role of autophagy in the pathogenesis of CRS …”
Section: Introductionmentioning
confidence: 99%
“…9 Very recently, three preliminary studies have reported conflicting results regarding the autophagy status in nasal polyp-derived fibroblast, arguing for further investigations on the role of autophagy in the pathogenesis of CRS. [11][12][13] In mammals, the conversion of autophagic effector protein microtubule-associated protein 1 light chain 3B (LC3B) from LC3B-I (free form) to LC3B-II (membrane-bound lipidated form) is a critical step in the induction of autophagy. Therefore, LC3B-II serves as a widely used marker of the autophagosome.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is an important cellular pathway for the maintenance of homeostasis. It degrades damaged organelles, misfolded proteins and damaged DNA to provide energy that allows the cells to respond to adverse environments (11,12). Autophagy is closely associated with inflammation (13) and is induced by a variety of inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%